(untitled) (Per Musi, 2000)
Based on the evidence that the process of transcription in music and literature (particularly in poetry) has a lot common aspects and characteristics, the text searches in the theory of translation for elements which may strengthen the critical analysis of musical transcription. Some concepts, such as work, originality, interpretation and authorship are discussed as fundamental in the understanding of the phenomenum of transcription. The close relation between transcription and interpretation is especially pointed out, since it has decisive influence on the comprehension of the musical piece.